Breast and cervical cancers awareness and screening practices among rural women in Ona-ara Local government area, Ibadan, Nigeria (2013)
The level of awareness and screening practices for breast and cervical cancers among rural women was investigated. Three of the six rural wards in Ona-ara LGA were selected by balloting and the three largest communities in each of the wards were purposively selected for the study.Structured interview was conducted among 276 consenting women aged ≥18 years in the households. Data were analysed using descriptive statistics and Chi-square test. Mean age of respondents was 36.5+12.6 years. Only 52(18.8%) and 11(4.0%) mentioned they knew something about breast and cervical cancers respectively. Knowledge of risk factors, cause and screening methods was poor irrespective of demographics. Only 15/52 (28.8%) and 3/52 (5.8%) who knew something about breast cancer mentioned clinical and Breast Self-Examination (BSE) respectively as screening methods for breast cancer. Half, 28/52 (53.8%) have ever practiced BSE and 9(17.3%) had clinical examination of the breast which was done as part of antenatal care or physical examination. The 24 respondents who did not examine their breasts mentioned they did not know they should (54.2%), don’t have problems with their breasts (54.3%), don’t know how to do it (37.5%) and think health workers should do it (33.3%). Only 4/11(36.4%) of those who knew something about cervical cancer mentioned vaginal examination for cervical cancer screening and only one (0.1%) respondent mentioned Pap smear. The poor level of awareness and screening practices for breast and cervical cancers among women in these rural communities emphasizes the need for community-based educational campaigns and provision of screening facilities in rural areas